[tex] {x}^{2} - 4x + 3 = 0[/tex]
[tex]a = 1[/tex]
[tex]b = - 4[/tex]
[tex]c = 3[/tex]
[tex]delta = {b}^{2} - 4ac[/tex]
[tex]delta = {( - 4)}^{2} - 4 \times 1 \times 3[/tex]
[tex]delta = 16 - 12[/tex]
[tex]delta = 4[/tex]
[tex]x(1,2) = \frac{ - b + - \sqrt{delta} }{2a} [/tex]
[tex]x(1,2) = \frac{ - ( - 4) + - \sqrt{4} }{2 \times 1} [/tex]
[tex]x(1,2) = \frac{4 + - 2}{2} [/tex]
[tex]x(1) = \frac{4 + 2}{2} [/tex]
[tex]x(1) = \frac{6}{2} [/tex]
[tex]x(1) = 3[/tex]
[tex]x(2) = \frac{4 - 2}{2} [/tex]
[tex]x(2) = \frac{2}{2} [/tex]
[tex]x(2) = 1[/tex]